Design and In Silico and In Vitro Evaluations of a Novel Nicotinamide Derivative as a VEGFR-2 Inhibitor - Ibrahim H. Eissa; Muhammad Abd ElGayed Bkrah; Reda G. Yousef; Hazem Elkady; Eslam B. Elkaeed; Bshra A. Alsfouk; Ibrahim M. Ibrahim; Ahmed M. Metwaly; Dalal Z. Husein (Journal of Chemistry)
A new nicotinamide derivative, (E)-N-(4-(1-(2-(4-benzamidobenzoyl)hydrazone)ethyl)phenyl)nicotinamide, was designed as a VEGFR-2 inhibitor. Utilizing the density functional theory (DFT) calculations, the three-dimensional structure of the designed compound was determined, shedding light on its stability and reactivity. Molecular docking revealed its capability to inhibit VEGFR-2, which was further supported by molecular dynamics (MD) simulations confirming its binding to the target protein. In addition, molecular mechanics-generalized born surface area (MM-GBSA), protein-ligand interactions profiler (PLIP), and essential dynamics studies provided further validation of the compound’s precise binding with optimal energy. Then, the “compound 10” was synthesized and subjected to in vitro assays. Compound 10 inhibited VEGFR-2 with an IC50 value of 105.4 ± 0.896 nM, comparing sorafenib’s IC50 value of 61.65 ± 0.934 nM. Besides, it exhibited cytotoxicity against HepG2 and MCF-7 cancer cell lines, with IC50 values of 35.78 ± 0.863 μM and 57.62 μM ± 0.871, comparing sorafenib’s IC50 values of 5.95 ± 0.917 μM and 8.45 ± 0.912 μM. Furthermore, compound 10 demonstrated a lower level of toxicity towards Vero cell lines, with an IC50 value of 127.3 μM. Likewise, compound 10 induced apoptosis in HepG2 cell lines through a flow cytometric analysis in addition to an increase in the levels of caspase-3 and caspase-9. Moreover, compound 10 hindered the migration and healing abilities of HepG2 cells. In conclusion, our study positions compound 10 as a promising candidate for further chemical modifications and biological evaluations.